2016
DOI: 10.1186/s12868-016-0307-2
|View full text |Cite
|
Sign up to set email alerts
|

A method for isolation of cone photoreceptors from adult zebrafish retinae

Abstract: BackgroundCone photoreceptors are specialised sensory retinal neurons responsible for photopic vision, colour perception and visual acuity. Retinal degenerative diseases are a heterogeneous group of eye diseases in which the most severe vision loss typically arises from cone photoreceptor dysfunction or degeneration. Establishing a method to purify cone photoreceptors from retinal tissue can accelerate the identification of key molecular determinants that underlie cone photoreceptor development, survival and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“… 32 , 33 Previous data confirm that in zebrafish, hdac6 is expressed in the larval eye during maturation of visual function, 19 and specifically in cone photoreceptors as determined by microarray analysis of cone-enriched transcripts from adult zebrafish. 34 The data are deposited in the NCBI Gene Expression Omnibus (GEO) database, under accession number GSE86155. Furthermore, in a recent study Pinho et al 35 have demonstrated that zebrafish HDAC6 shows high sequence identity with the mammalian homolog at its deacetylase active site.…”
Section: Resultsmentioning
confidence: 99%
“… 32 , 33 Previous data confirm that in zebrafish, hdac6 is expressed in the larval eye during maturation of visual function, 19 and specifically in cone photoreceptors as determined by microarray analysis of cone-enriched transcripts from adult zebrafish. 34 The data are deposited in the NCBI Gene Expression Omnibus (GEO) database, under accession number GSE86155. Furthermore, in a recent study Pinho et al 35 have demonstrated that zebrafish HDAC6 shows high sequence identity with the mammalian homolog at its deacetylase active site.…”
Section: Resultsmentioning
confidence: 99%
“…The dataset was validated by qPCR of 45 transcripts, and many transcripts present in rods were not previously recognized as rod-enriched. Analysis of FACS-sorted fluorescent rods from transgenic zebrafish appears to be an excellent approach for expanding our knowledge of rod biology, and in the future may be applied to other photoreceptor subpopulations [ 63 ], since there are numerous transgenic tools available that selectively fluorescently label specific cone subtypes [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…At different time points after injury induction (1, 3, and 7 dpli), both retinas of three gfap:gfap-GFP zebrafish per time point were dissected and kept in cold diethyl pyrocarbonate phosphate-buffered saline (DEPC-PBS) (Glaviano et al 2016 ). Enzymatic dissociation was initiated by 0.05% trypsin (ThermoFisher Scientific) diluted in DEPC-PBS at 37 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%